Cash Flow Ratios for Evaluating Performance in Nepalese Commercial Banks - Naba Raj Adhikari (Journal of Balkumari College, 2022)
The purpose of this paper is to examine and analyze the performance of Nepalese commercial banks through cash flow ratios. Descriptive as well as analytical research design has been used. All the government owned commercial banks has been taken as the sample of the study using judgmental technique. Sufficiency and efficiency ratios has been used for evaluating the performance of the concerned commercial banks. Data have been collected through the annual reports of respective banks covering for the financial year 2017/2018 to 2019/2020. All the banks are efficient to generate operating cash flow from sales and continued activities. However the cash generation from continued activities and asset utilization revealed sound in NBL and RBB than ADB in 2019/2020. Cash flow sufficiency revealed similar trends in all banks.